Direct actions and arbitration: all at sea - Briggs, Adrian (Lloyd's Maritime and Commercial Law Quarterly, 2016)

Joint Development of Offshore Polar Oil and Gas Resources and the United Nations Convention on the Law of the Sea - Abrahamson, John (Australian National University, 2015)
This thesis examines whether the establishment of Joint Development Zones (JDZs) for the development of offshore oil and gas resources in the Arctic and Southern Oceans can effectively resolve competing continental shelf and outer continental shelf (OCS) claims arising under the provisions of Article 76 of the United Nations Convention on the Law of the Sea (LOSC). One of the effects of global warming has been increased interest in oil and gas activity in the Arctic region, however there is significant concern as to the related environmental risks. The Environmental Protocol to the Antarctic Treaty currently suspends exploration for state parties for oil and gas in the Southern Ocean, however current exploration has been reported. A JDZ may be defined as an inter-governmental arrangement of a provisional or permanent nature, designed for joint exploration and exploitation of the hydrocarbon resources of the sea-bed. JDZs are generally based on agreements to suspend sovereignty claims and share offshore oil and gas in the JDZ region. The thesis was prepared to contribute to the prevention of potential international conflicts over offshore oil and gas resources. State claims may be based on historic claims, interpretation of treaties, and LOSC exclusive economic zone (EEZ), continental shelf, and OCS delimitation provisions. LOSC provides dispute resolution alternatives, including referral to the International Court of Justice and international arbitration. A significant number of states have, however, preferred to adopt JDZ agreements. The methods used for the thesis included analysis of LOSC maritime delimitation provisions, existing JDZ agreements, the terms of model JDZ agreements, and analysis of current Arctic and Southern ocean maritime boundary disputes. The principal thesis conclusions are: - JDZs can resolve resource disputes as demonstrated by the existing international state practice in adopting JDZs. JDZ regimes are not a universal panacea, however, and successful JDZs are based on the continued political support of the respective states; - LOSC maritime boundary delimitation provisions may not resolve boundary disputes, which can arise due to issues including conflicting sovereignty of land territory; - Specific Arctic and Southern Ocean disputed regions have similar characteristics to existing JDZs. JDZs may therefore potentially apply to resolve these disputes; - JDZs can potentially provide solutions for disputed boundaries, such as between United States/Canada (Beaufort Sea), United States/Russia (Bering Sea) in the Arctic Ocean region, and between United Kingdom/Argentina/Chile in the Southern Ocean; - JDZ should be adapted to better protect and preserve the marine environment, and to provide a significant liability regime similar to the Greenland regime; - JDZs should support a framework of regional governance, including Arctic Council or Antarctic Treaty representation in the respective JDZs; and - Potential game changing events may affect the use of JDZs in the future, including political and technological developments, and significant oil and gas discoveries. The result of the thesis conclusions is to prove the hypothesis that JDZs can effectively resolve resource conflicts in the Arctic and Southern Ocean regions.

International convention for the control and management of ships' ballast water and sediments, 2004 - Robe Hughes, Charlotte (Aix-Marseille Université, 2011)
Will harmonization of legislation relating to the management of ships’ ballast water be achieved, once IMOs’ 2004 Convention enters into force?